2007
DOI: 10.1055/s-2006-924646
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Results of Operative and Conservative Treatment of Deep Dermal Partial-Thickness Scalds in Children

Abstract: Deep dermal partial-thickness scalds remain one of the most common types of injuries in childhood. Local treatment of those wounds, alternatively described as IIb degree, is still very controversial. Some authors advise conservative treatment of such wounds, pointing to their ability to self-reepithelialise, which is possible but significantly prolonged. Other investigators postulate operative treatment, i.e., tangential necrectomy and split-thickness autologous skin grafting, which may shorten the time of wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…In vitro and in vivo studies have shown that silver has a cytotoxic effect against rapidly proliferating cells, including keratinocytes and fibroblasts, and thus may delay wound epithelialization 8,13. However, clinical studies in patients with partial-thickness wounds (partial-thickness burns and skin graft donor-sites) demonstrated good wound re-epithelialization, with no delay in wound healing 27,28,3237. Moreover, an in-vivo infected wound model demonstrated similar wound healing properties between Aquacel and Aquacel Ag ® , with significant lower bacterial loads in the Aquacel Ag ® treated group 25.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro and in vivo studies have shown that silver has a cytotoxic effect against rapidly proliferating cells, including keratinocytes and fibroblasts, and thus may delay wound epithelialization 8,13. However, clinical studies in patients with partial-thickness wounds (partial-thickness burns and skin graft donor-sites) demonstrated good wound re-epithelialization, with no delay in wound healing 27,28,3237. Moreover, an in-vivo infected wound model demonstrated similar wound healing properties between Aquacel and Aquacel Ag ® , with significant lower bacterial loads in the Aquacel Ag ® treated group 25.…”
Section: Discussionmentioning
confidence: 99%
“…Silver-containing dressings are relatively expensive, although the higher cost is partially offset by; reduced use of secondary gauze, retention dressings, and improved wound healing together with the reduced costs of other care. Cost-effectiveness calculations comparing Aquacel Ag ® to standard of care in patients with acute and chronic wounds showed favorable results using Aquacel Ag ® 27,32,33,3638…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, results were not stratified for superficial and deep partial thickness burns, because the study area was often partial thickness burns with different depth. This distinction is important because some authors postulate that standard operative treatment for the deep partial thickness burns minimizes poor scar quality, although, there is no consensus in the literature regarding timing and type of the operation, debridement technique, use of skin substitutes or application of growth factors and other humoral agents to enhance wound healing . Spontaneous wound healing of deep partial thickness burns is still possible because of the surviving keratinocytes and epidermal stem cells in the remaining dermis layer .…”
Section: Discussionmentioning
confidence: 99%